Guinea pig transglutaminase immunolinked assay does not predict coeliac disease in patients with chronic liver disease. Issue 4 (1st October 2001) - Carroccio, A; Giannitrapani, L; Soresi, M; Not, T; Iacono, G; Di Rosa, C; Panfili, E; Notarbartolo, A; Montalto, G
Abstract : BACKGROUND: It has been suggested that serological screening for coeliac disease (CD) should be performed in patients with chronic unexplained hypertransaminasaemia. AIMS: To evaluate the specificity for CD diagnosis of serum IgA antitissue transglutaminase (tTG) determination in consecutive patients with chronic hypertransaminasaemia using the most widely utilised ELISA based on tTG from guinea pig as the antigen. PATIENTS AND METHODS: We studied 98 patients with chronic hypertransaminasaemia, evaluated for the first time in a hepatology clinic. Serum anti-tTG and antiendomysial (EmA) assays were performed. Patients positive for EmA and/or anti-tTG were proposed for intestinal biopsy. Finally, all sera were reassayed for anti-tTG using an ELISA based on human recombinant tTG as the antigen. RESULTS: A total of 94/98 hypertransaminasaemic patients were positive for hepatitis virus markers, with 82/98 (83%) positive for anti-hepatitis C virus. Liver histology showed that most patients had mild or moderate chronic hepatitis while severe fibrosis or overt liver cirrhosis was found in 20/98. CD screening showed that 15/98 (16%) hypertransaminasaemic subjects had anti-tTG values in the same range as CD patients; however, IgA EmA were positive in only 2/98 (2%). Distal duodenal biopsy, performed in nine patients, showed subtotal villous atrophy in the two EmA+/anti-tTG+ patients but was normal in 7/7 EmA−/anti-tTG+ subjects. The presence of anti-tTG+ values in EmA− patients was unrelated to particular gastrointestinal symptoms, other associated diseases, severity of liver histology, or distribution of viral hepatitis markers. There was a significantly higher frequency of positive serum autoantibodies (antinuclear, antimitochondrial, antismooth muscle, and anti-liver-kidney microsomal antibodies) in anti-tTG+/EmA− patients than in the other subjects (9/13 v 10/83; p<0.003). Also, a correlation was found between serum gamma globulin and anti-tTG values (p<0.01). When sera were tested with the ELISA based on human tTG as the antigen, no false positive results were observed: only the two EmA+ patients with atrophy of the intestinal mucosa were positive for anti-tTG while all others were negative, including those false positive in the ELISA based on guinea pig tTG as the antigen. CONCLUSIONS: In patients with elevated transaminases and chronic liver disease there was a high frequency of false positive anti-tTG results using the ELISA based on tTG from guinea pig as the antigen. Indeed, the presence of anti-tTG did not correlate with the presence of EmA or CD. These false positives depend on the presence of hepatic proteins in the commercial tTG obtained from guinea pig liver and disappear when human tTG is used as the antigen in the ELISA system. We suggest that the commonly used tTG ELISA based on guinea pig antigen should not be used as a screening tool for CD in patients with chronic liver disease.